Glycoprotein D or J Delivered in trans Blocks Apoptosis in SK-N-SH Cells Induced by a Herpes Simplex Virus 1 Mutant Lacking Intact Genes Expressing Both Glycoproteins - Zhou, Guoying (American Society for Microbiology, 2000)
We have made two stocks of a herpes simplex virus 1 mutant lacking intact U(S)5 and U(S)6 open reading frames encoding glycoproteins J (gJ) and D (gD), respectively. The stock designated gD(−/+), made in cells carrying U(S)6 and expressing gD, was capable of productively infecting cells, whereas the stock designated gD(−/−), made in cells lacking viral DNA sequences, was known to attach but not initiate infection. We report the following. (i) Both stocks of virus induced apoptosis in SK-N-SH cells. Thus, annexin V binding to cell surfaces was detected as early as 8 h after infection. (ii) U(S)5 or U(S)6 cloned into the baculovirus under the human cytomegalovirus immediate-early promoter was expressed in SK-N-SH cells and blocked apoptosis in cells infected with either gD(−/+) or gD(−/−) virus, whereas glycoprotein B, infected cell protein 22, or the wild-type baculovirus did not block apoptosis. (iii) In SK-N-SH cells, internalized, partially degraded virus particles were detected at 30 min after exposure to gD(−/−) virus but not at later intervals. (iv) Concurrent infection of cells with baculoviruses did not alter the failure of gD(−/−) virus from expressing its genes or, conversely, the expression of viral genes by gD(−/+) virus. These results underscore the capacity of herpes simplex virus to initiate the apoptotic cascade in the absence of de novo protein synthesis and indicate that both gD and gJ independently, and most likely at different stages in the reproductive cycle, play a key role in blocking the apoptotic cascade leading to cell death.